Sex-related disparities in outcomes of cholangiocarcinoma patients in treatment trials - Ledenko, Matthew; Antwi, Samuel O.; Arima, Shiho; Driscoll, Julia; Furuse, Junji; Klümpen, Heinz-Josef; Larsen, Finn Ole; Lau, David K.; Maderer, Annett; Markussen, Alice; Moehler, Markus; Nooijen, Lynn E.; et al. (Frontiers in Oncology, 2022)
Background & aims. Cholangiocarcinoma (CCA) has historically been treated without regard to patient’s biological sex. Although males and females differ considerably in physiology and drug metabolism, the effect of patient sex on treatment outcomes is unknown. The aim of this study was to understand the impact of biological sex on treatment outcomes of cholangiocarcinoma patients. Methods. A systematic search for clinical trials on CCA patents was performed on PubMed.gov, Clinicaltrials.gov, Cochrane Central Register of Controlled Trials, EMBASE via Ovid, the World Health Organization’s International Clinical Trial Registry Platform, and Google Scholar. Results. One hundred and eighty-four studies were concordantly selected by two independent reviewers and the raw data for these studies were requested from the corresponding authors by email. Fifteen studies provided detail data for 19 independent groups of CCA patients treated with different chemotherapeutic agents. Females had higher overall survival in thirteen of the nineteen groups, whereas males had higher overall survival in only two of the groups. Progression-free survival was similar in females and males. Conclusions. There are sex-related disparities in overall survival of CCA patients enrolled in treatment trials, which could be due to sex differences in physiology and metabolism. The findings support incorporating sex as a biological variable in the design of future clinical trials for CCA.